Foreign direct investment and research & development activity: the role of competition - Tan, Boon Yee; Wan Ngah, Wan Azman Saini (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper investigates the relationship between foreign direct investment (FDI) and domestic research and development (R&D) activity, conditional on product market competition. The generalized Method of Moments (GMM) panel estimator is used to analyze the relationship using a sample of 61 countries over the 2000-2011 periods. The result reveals that FDI has little direct effect on R&D expenditure, but its effect manifests negatively conditional on competition. The finding contradicts with conventional wisdom regarding merits of competition as our evidence shows that competition undermines the effect of FDI on domestic R&D.